The effect of Moringa oleifera leaf extract in feed as an immunostimulant for Aeromonas hydrophilla bacterial infections - Imelda Arisa Iko; Faradila Maisa; Mellisa Siska (BIO Web of Conferences)
This study investigates the impact of adding Moringa oleifera leaf extract to feed as an immunostimulant for tilapia infected with Aeromonas hydrophila. The experiment followed a Completely Randomized Design (CRD) with six treatments and three replications. The findings revealed that incorporating Moringa leaf extract significantly influenced survival rates (P<0.05). The highest survival rate (83.33%) was observed with a dose of 150 mg kg-1. In conclusion, doses of 100-150 mg kg-1 of Moringa leaf extract produced the best results, including reduced clinical symptoms, survival rates (70-83.33%), leukocyte count (173-223 x 103 cells mm-3), hematocrit (27-28%), and hemoglobin levels (6.6-7 g dL-1), indicating its potential as an effective immunostimulant for tilapia.